Iterative Solutions for Alternate Depths in Open Channels - Nayak, Sudam Chandra; Senapati, Sagar Chandra; Sahu, Ambika Prasad (Journal of Agricultural Engineering, 2009)
Computation of alternate depths (super-critical and sub-critical) for a specific energy was mathematically solved by iteration method for trapezoidal, rectangular, triangular and parabolic channels. The computed values were compared with the graphical method suggested by Chow (1959). The values obtained from graphical method were very close with the values computed by iteration method with variations from -0.20 to 0.40 and -1.38 to 1.00 for sub-critical and super-critical depths, respectively. This justified the correctness and suitability of the iteration method to find out the two alternate depths for a specific energy for different channels.